What MMO Communities Don’t Do: A Longitudinal Study of Guilds and Character Leveling, Or Not - Poor, Nathaniel (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Guilds, a primary form of community in many online games, are thought to both aid gameplay and act as social entities. This work uses a three-year scrape of one game, World of Warcraft, to study the relationship between guild membership and advancement in the game as measured by character leveling, a defining and often studied metric. 509 guilds and 90,581 characters are included in the analysis from a three-year period with over 36 million observations, with linear regression to measure the effect of guild membership. Overall findings indicate that guild membership does not aid character leveling to any significant extent. The benefits of guilds may be replicated by players in smaller guilds or not in guilds through game affordances and human sociability.